T cell densities in brain metastases are associated with patient survival times and diffusion tensor MRI changes - Zakaria, Rasheed (Cancer Res, 2017)
Brain metastases are common and are usually detected by magnetic resonance imaging (MRI). Diffusion tensor imaging (DTI) is a derivative MRI technique which can detect disruption of white matter tracts in the brain. We have matched preoperative DTI with image-guided sampling of the brain-tumor interface in 26 patients during resection of a brain metastasis and assessed mean diffusivity (MD) and fractional anisotropy (FA). The tissue samples were analysed for vascularity, inflammatory cell infiltration, growth pattern, and tumor expression of proteins associated with growth or local invasion such as Ki67, S100A4, and MMP2, 9, and 13. A lower FA in the peritumoral region indicated more white matter tract disruption and independently predicted longer overall survival times (HR for death = 0.21, 95% CI 0.06 - 0.82, p=0.024). Of all the biological markers studied, only increased density of CD3+ lymphocytes in the same region correlated with decreased FA (Mann Whitney U, p=0.037) as well as confounding completely the effect of FA in multivariate survival analyses. We conclude that the T cell response to brain metastases is not a surrogate of local tumor invasion, primary cancer type, or aggressive phenotype and is associated with patient survival time regardless of these biological factors. Furthermore, it can be assayed by DTI, potentially offering a quick, non-invasive, clinically available method to detect an active immune microenvironment and, in principle, to measure susceptibility to immunotherapy.